Приближенный расчет сверхсильных электрических и сильных магнитных полей в атоме вещества - Баранов, Михаил Иванович (НТУ "ХПИ", 2006)
Приведены результаты оценочных расчетов сверхсильных электрических и сильных магнитных полей в простейшем атоме вещества – атоме водорода, основанные на усовершенствованной автором квантовомеханической модели атома Бора.

Results of evaluation calculations of ultrahigh electric and high magnetic fields in the simplest material atom, a hydrogen atom, are given, the calculation based on Bohr's quantum-mechanical model of the atom improved by the author.
Approximate calculation of ultrahigh electric and high magnetic fields in a material atom
Keywords: атомная физика; квантовая механика; атомы вещества; молекулы вещества; атомы водорода; строение вещества; квантовая электродинамика; электростатическое поле; hydrogen atom; ultrahigh electric field; high magnetic field; strength and density of electric field energy; strength and densityof magnetic field energy